Magnetic Resonance Neurography Reveals Smoking-Associated Decrease in Sciatic Nerve Structural Integrity in Type 2 Diabetes - Jende, Johann M. E.; Mooshage, Christoph; Kender, Zoltan; Kopf, Stefan; Groener, Jan B.; Heiland, Sabine; Juerchott, Alexander; Nawroth, Peter; Bendszus, Martin; Kurz, Felix T. (Frontiers in Neuroscience, 2022)
Objective: It is controversially discussed in how far smoking contributes to diabetic polyneuropathy (DPN) in type 2 diabetes (T2D). Diffusion-weighted magnetic resonance neurography (MRN) at 3 Tesla has been shown to provide objective values for structural nerve integrity in patients with T2D. The aim of this study was to investigate the contribution of cigarette smoking on structural nerve integrity in T2D. Methods: This cross-sectional prospective cohort study investigated the structural integrity of the sciatic nerve in 10 smokers, 40 never-smokers, and 20 ex-smokers with T2D and 10 healthy control subjects, using diffusion tensor imaging MRN at 3 Tesla and semi-automated nerve fiber tracking. Results were correlated with clinical, electrophysiological, and serological data. Results: The sciatic nerve’s fractional anisotropy (FA), a parameter for structural nerve integrity, was significantly lower in smokers with T2D when compared to controls (p=0.002) and never-smokers (p=0.015), and lower in ex-smokers when compared to controls (p=0.015). In addition, sciatic nerve radial diffusivity, a marker of myelin damage, was increased in smokers versus controls and never-smokers (p=0.048, p=0.049, respectively). Furthermore, FA in T2D patients was negatively correlated patients with clinical and electrophysiological markers of DPN. FA also showed negative correlations with the pulse wave velocity, a marker of arterial stiffness and associated microangiopathy, in controls (r=0.-70; p=0.037), never-smokers (r=-0.45; p=0.004), ex-smokers (r=-0.55; p=0.009), and a similar trend in smokers (r=-0.63; p=0.076). Negative correlations were found between FA and skin auto-fluorescence, a marker of tissue advanced glycation end product accumulation and therefore long-term glycemic stress in T2D, in never-smokers (r=-0.39; p=0.020) and smokers (r=-0.84; p=0.004), but not in ex-smokers (r=-0.07; p=0.765). Conclusions: The findings indicate that smoking contributes to sciatic nerve damage in T2D, potentially worsening DPN due to glycemic stress and less microangiopathy associated myelin damage in active smokers, while angiopathic effects predominate in ex-smokers. To stop smoking may therefore pose a promising preventive measure to slow the progression of DPN in T2D.